Tetramethylpyrazine attenuates the blood-brain barrier damage against ischemic stroke by targeting endothelin-1/Akt pathway in astrocytes - Deng, Minzhen; Cai, Yuefang; Wang, Yu; Hu, Dafeng; Li, Yan; Ning, Zhenqiu; Wang, Chengyi; Chung, Sookja Kim; Huang, Yan; Sun, Jingbo; Zhou, Lihua; Li, Jie; et al. (Frontiers in Pharmacology, 2025)
Our study focused on the role of traditional Chinese medicine in stroke therapy, specifically targeting endothelin-1 (ET-1) in astrocytes to alleviate ischemic brain injury. Utilizing oxygen-glucose deprivation/reoxygenation (OGD/R) and middle cerebral artery occlusion (MCAO) models, we mimicked cerebral ischemia in both cell cultures and mice. Tetramethylpyrazine (TMP), a component of the Chinese medicine, was identified as a potential therapeutic agent. It significantly increased cell viability, reduced ET-1 expression, and mitigated OGD-induced astrocyte damage, as shown by in vitro experiments with ET-1 siRNA and cell lines overexpressing ET-1. In the MCAO animal model, TMP improved neurological scores, decreased infarct size, and lowered ET-1 levels, thus strengthening the blood-brain barrier and reducing oxidative stress. TMP’s neuroprotective effects were further linked to the upregulation of phosphorylated AKT (p-AKT), indicating that the AKT pathway may function downstream of ET-1. These results highlight TMP’s potential in treating ischemic stroke by modulating the ET-1 and AKT signaling pathways, offering a promising avenue for future stroke therapies.